Audiological biomarkers of tinnitus in an older Portuguese population - Haider, Haúla F (2022)
Funding: HH and DR had received a Ph.D. grant from Jmellosaude. DH was funded by the National Institute for Health Research (NIHR) Biomedical Research Centre program. The present publication was funded by Fundação Ciência e Tecnologia, IP national support through CHRC (UIDP/04923/2020).